Study on the Fluidization of Mixture of Plastic Waste and Alumina - Saraceno, Emilia; Renda, Simona; Menéndez, Miguel; Palma, Vincenzo (Jornada de Jóvenes Investigadores del I3A, 2025)
This study explores the fluidization of systems composed of plastic waste and alumina – in different ratios and ranges of porous distribution – to assess the possibility of using a fluidized bed reactor for the catalytic conversion of plastic waste. A model for the prediction of the minimum fluidization velocity is proposed.